Genetic European Ancestry and Incident Diabetes in Black Individuals: Insights From the SPRINT Trial. (28th January 2022) - Parcha, Vibhu; Heindl, Brittain; Kalra, Rajat; Bress, Adam; Rao, Shreya; Pandey, Ambarish; Gower, Barbara; Irvin, Marguerite R.; McDonald, Merry-Lynn N.; Li, Peng; Arora, Garima; Arora, Pankaj
Abstract : Background: Black individuals have high incident diabetes risk, despite having paradoxically lower triglyceride and higher HDL (high-density lipoprotein) cholesterol levels. The basis of this is poorly understood. We evaluated the participants of SPRINT (Systolic Blood Pressure Intervention Trial) to assess the association of estimated European genetic ancestry with the risk of incident diabetes in self-identified Black individuals. Methods: Self-identified non-Hispanic Black SPRINT participants free of diabetes at baseline were included. Black participants were stratified into tertiles (T1–T3) of European ancestry proportions estimated using 106 biallelic ancestry informative genetic markers. The multivariable-adjusted association of European ancestry proportion with indices of baseline metabolic syndrome (ie, fasting plasma glucose, triglycerides, HDL cholesterol, body mass index, and blood pressure) was assessed. Multivariable-adjusted Cox regression determined the risk of incident diabetes (fasting plasma glucose ≥126 mg/dL or self-reported diabetes treatment) across tertiles of European ancestry proportion. Results: Among 2466 Black SPRINT participants, a higher European ancestry proportion was independently associated with higher baseline triglyceride and lower HDL cholesterol levels ( P <0.001 for both). European ancestry proportion was not associated with baseline fasting plasma glucose, body mass index, and blood pressure ( P >0.05). Compared with the first tertile, those in the second (hazard ratio, 0.64 [95% CI, 0.45–0.90]) and third tertiles (hazard ratio, 0.61 [95% CI, 0.44–0.89]) of the European ancestry proportion had a lower risk of incident diabetes. A 5% point higher European ancestry was associated with a 29% lower risk of incident diabetes (hazard ratio, 0.71 [95% CI, 0.55–0.93]). There was no evidence of a differential association between the European ancestry proportion tertiles and incident diabetes between those randomized to intensive versus standard blood pressure treatment. Conclusions: The higher risk of incident diabetes in Black individuals may have genetic determinants in addition to adverse social factors. Further research may help understand the interplay between biological and social determinants of cardiometabolic health in Black individuals. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT01206062.